2017
DOI: 10.1177/1071100717719533
|View full text |Cite
|
Sign up to set email alerts
|

Pathoanatomy and Associated Injuries of Posterior Malleolus Fracture of the Ankle

Abstract: Level III, retrospective comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 30 publications
(23 reference statements)
1
103
0
1
Order By: Relevance
“…The use of an additional buttress plate is advised in case of a large posterior fragment (> 25%) and long proximal extension. Recently, three CT-based classification systems of posterior malleolar fractures were developed [1416]. With increasing stage the need for anatomical reduction and fixation increases to restore intra-articular unevenness.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an additional buttress plate is advised in case of a large posterior fragment (> 25%) and long proximal extension. Recently, three CT-based classification systems of posterior malleolar fractures were developed [1416]. With increasing stage the need for anatomical reduction and fixation increases to restore intra-articular unevenness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors include in the analysis pilon fractures, which have a very different pathomechanism. Mason et al [25] divided the fractures into 3 groups based on severity and pathomechanics. Type 1 is an extra-articular posterior malleolar fragment, type 2 involves a primary fragment of the Volkman area with or without a medial injury, and type 3 is a fracture in the coronal plane that includes all the plafond.…”
Section: Discussionmentioning
confidence: 99%
“…Mason et al have suggested a classification system of posterior malleolar fractures that progresses in severity, indicating the pathomechanics of the fracture and then guides surgical fixation. 17 Attempting to address the syndesmosis without reduction and stabilisation of the posterior malleolus often results in malreduction of the syndesmosis.…”
Section: Discussionmentioning
confidence: 99%